Identifikasi cultural landscape di Desa Bayung Gede, Kabupaten Bangli, Provinsi Bali - Anggawirya, Anak Agung Bagus Bayu; Paturusi, Syamsul Alam; Trimarianto, Ciptadi (Jurnal Arsitektur Lansekap, 2021)
Landscape and culture are important for the sustainability of Bali tourism. The combination of landscape and culture forms a cultural landscape. For the environment, cultural landscape sustainability is very important because it contributes to biodiversity conservation. Bayung Gede Village is a Bali Aga village located in a mountainous area, with geographic conditions consisting of traditional settlements and plantation land. Bayung Gede Village has various uniqueness, but the utilization of its potential for tourism is not optimal. This research is an attempt to identify the potential cultural landscape in Bayung Gede Village. The research method used is qualitative research methods. Data collection techniques were carried out through field observations, in-depth interviews, and literature studies. The data were analyzed by using descriptive analysis techniques. From the analysis, it is concluded that most of the Bayung Gede Village area is a cultural landscape. The unique cultural landscape in Bayung Gede Village is in the form of traditional residential areas, traditional house yards, and sacred spaces. The cultural landscape of Bayung Gede Village is a cultural landscape that is deliberately designed by humans, and an associative cultural landscape, which is a combination of nature and people's beliefs.